Emerging Middle Power dan Tantangan Perwujudan Visi Indonesia 2045 di Asia Pasifik: Systematic Review [Emerging Middle Power and Challenges on Realizing Vision of Indonesia 2045 in Asia Pacific: Systematic Review] - Aristama, Ferga (Sekretariat Jenderal DPR RI, 2022)
Amid the limited leverage in Southeast Asia, Indonesia’s ambition to be the most influential state in the Asia Pacific calls into doubt. Hence, this study explores the challenges in realizing the four targets of Vision of Indonesia 2045 in the Asia Pacific. While previous research has broadly identified the challenges in this region, no study categorizes them into those targets by detailing the literatures used as a source of knowledge and how to obtain them. As analytical frameworks, this study uses the concept of Vision of Indonesia 2045: Indonesia as One of Asia Pacific’s Most Influential States (Ministry of National Development Planning, 2019) and Emerging Middle Power in Regional and Global Governance (Öniş & Kutlay, 2017). Furthermore, this study uses a qualitative approach through a systematic review that refers to the Preferred Reporting for Systematic Reviews and Meta-Analyses 2020 (PRISMA 2020) and the content analysis method with Atlas.ti 22. Based on the analysis, this study found 172 quotes interpreted into 17 internal and 31 external factors that challenge four Indonesia targets of Vision of Indonesia 2045: maximizing national interests in the Asia Pacific, establishing regional order, generating ideas and challenges to lead and play a role in work forums. Two internal factors—military capacity and national infrastructure—and two external factors—the rise of China and competence among great powers—are the most highlighted. These factors indicate the broad impact on achieving Vision of Indonesia 2045 as one of Asia Pacific’s most influential states. Thus, as an implication, they need to be considered as inputs in formulating Indonesia’s foreign policy and strategy, including in the law formulation.AbstrakDi tengah belum maksimalnya peran Indonesia di Asia Tenggara, ambisi Indonesia menjadi negara paling berpengaruh di Asia Pasifik diragukan. Dengan permasalahan tersebut, penelitian ini mengeksplorasi tantangan Indonesia sebagai negara paling berpengaruh di Asia Pasifik dalam kerangka empat sasaran Visi Indonesia 2045. Penelitian terdahulu telah banyak mengidentifikasi tantangan regional Indonesia di Asia Pasifik, namun belum ada penelitian yang mengkategorisasi tantangan tersebut ke dalam empat sasaran Visi Indonesia 2045 dengan merinci pustaka yang digunakan dan bagaimana memperoleh sumber pengetahuan tersebut. Konsep Visi Indonesia 2045: Indonesia sebagai Negara Berpengaruh di Asia Pasifik (Kementerian PPN/Bappenas, 2019) dan Emerging Middle Power pada Tata Pemerintahan Regional dan Global (Öniş & Kutlay, 2017) digunakan sebagai landasan berpikir. Lebih lanjut, penelitian ini menggunakan pendekatan kualitatif melalui systematic review yang mengacu kepada Preferred Reporting for Systematic Review and Meta-Analyses 2020 (PRISMA 2020) dan metode content analysis dengan Atlas.ti 22. Berdasarkan analisis, penelitian ini menemukan 172 quote yang diinterpretasikan ke dalam 17 faktor internal dan 31 faktor eksternal menjadi tantangan atas sasaran visi Indonesia 2045: maksimalisasi kepentingan nasional di Asia Pasifik, membentuk tatanan regional, menghasilkan gagasan serta tantangan memimpin dan berperan dalam forum kerja sama. Dua faktor internal—kapasitas militer dan infrastruktur nasional—dan dua faktor eksternal—kebangkitan Tiongkok dan kompetisi antar great power—adalah faktor yang mendapatkan banyak highlight. Hal ini mengindikasikan bahwa faktor-faktor tersebut berdampak luas kepada sasaran atas tercapainya Visi Indonesia 2045 sebagai salah satu negara paling berpengaruh di Asia Pasifik. Sebagai implikasinya, faktor-faktor tersebut penting untuk diperhatikan dalam penyusunan strategi dan kebijakan luar negeri di Indonesia termasuk dalam perumusan peraturan perundang-undangan.